الصراع التركي الفرنسي على إفريقيا وآثاره على ليبيا (2011 -2020 ) - بالحسن سيف النصر عبد السلام (Scientific Journal of University of Benghazi, 2021)
This paper deals with the reasons behind the Turkish-French rivalry and the conflict over Libya, which led to instability since the outbreak of the Libyan Revolution on February 17, 2011. Regional and international intervention increased in post-revolution Libya; the French intervention at the beginning of the revolution was followed by the Turkish intervention and the intensity of their rivalry reached its peak in recent years to near direct armed clashes between them for geopolitical reasons.